The degree of tooth color change using different concentrations of carbamide peroxide - Knežević, Nataša; Dolić, Olivera; Obradović, Marija; Kojić, Željka; Đeri, Aleksandra; Veselinović, Valentina; Sukara, Slava (Scripta Medica, 2019)
INTRODUCTION: Depending on the cause of discoloration, bleaching materials and other factors, vital dental bleaching techniques may be professional (in-office dental bleaching), at-home night-guard bleaching and combined. The main objective of this study was to determine, in vitro, tooth color change using external dental bleaching techniques with 16% and 30% carbamide peroxide gel and to investigate the effect of concentration of carbamide peroxide gel on the bleaching success. MATERIALS AND METHOD: This study included 20 extracted human intact teeth. The teeth were divided into two groups of ten teeth: the first group was bleached with 16% carbamide peroxide gel and the second group with 30% carbamide peroxide gel. The procedure was repeated three times for each tooth. The existing color of every tooth was recorded using VITA classical shade guide A1-D4 before treatment, after each session and after bleaching was completed. RESULTS: Exact binomial test found a highly statistically significant difference (p